Advances on remote sensing as supporting tool for hydrological management - Vázquez, A. L.; Oates, M. J.; Ruiz-Canales, A.; Molina-Martínez, J. M.; Fernández-Pacheco, D. G.; Ruiz-Peñalver, L.; Rodrigues, V. A. [UNESP] (My University, 2015)
Over the last decades remote sensing has become a very valuable tool for hydrology, especially in water management. This development is due to, on the one hand, the fast technological evolution registered on sensors and platforms, thus enabling resolutions (spatial, temporal, radiometric…) ever even thought about before and every day at a lower cost; on the other hand, methodological research has brilliantly followed technical advances, so that in a blink we have passed from eye crop identification to Geographic Information Systems and sophisticated physic-physiologic computer models. Nonetheless, Remote Sensing is not too much applied yet in the operational level; thence, there is still very much to do in order to improve user-friendliness, reliability and accuracy at every level, from the field point to the continent.
Keywords: Classification; Evapotranspiration; Groundwater; Hydrology; Mapping; Salinity; Water management